The axon-guidance roundabout gene alters the pace of the Drosophila circadian clock. - Berni, J.; Beckwith, E.J.; Fernández, M.P.; Ceriani, M.F. (European Journal of Neuroscience, 2008)
Great efforts have been directed to the dissection of the cell-autonomous circadian oscillator in Drosophila. However, less information is available regarding how this oscillator controls rhythmic rest-activity cycles. We have identified a viable allele of roundabout, robo(hy), where the period of locomotor activity is shortened. From its role in axon-pathfinding, we anticipated developmental defects in clock-relevant structures. However, robo(hy) produced minor defects in the architecture of the circuits essential for rhythmic behaviour. ROBO's presence within the circadian circuit strengthened the possibility of a novel role for ROBO at this postdevelopmental stage. Genetic interactions between pdf (01) and robo(hy) suggest that ROBO could alter the communication within different clusters of the circadian network, thus impinging on two basic properties, periodicity and/or rhythmicity. Early translocation of PERIOD to the nucleus in robo(hy) pacemaker cells indicated that shortened activity rhythms were derived from alterations in the molecular oscillator. Herein we present a mutation affecting clock function associated with a molecule involved in circuit assembly and maintenance.